Effect of protein and energy levels on faecal progesterone concentration in Sabi ewes during oestrus cycle - Muzvondiwa, J.V; Kamanda, M.T.; Nyamukanza, C.C.; Mutisi, C. (Midlands State University, 2014)
The study investigated the reliability of using faecal progesterone as an indicator of ovarian activity in Sabi ewes and how this is affected by level of feeding. Three diets were formulated to simulate feed availability in communal areas of Zimbabwe, a below maintenance diet, a maintenance diet and an above maintenance diet. Faecal and blood samples were collected from 18 ewes (six in each treatment) once every two days for two oestrus cycles in order to determine progesterone levels. Diet had a significant effect on the plasma progesterone concentration (P<0.05) and a non significant effect on faecal progesterone concentration (P>0.05). On all diets, faecal progesterone concentrations were higher than plasma progesterone concentration. The pattern of faecal and plasma progesterone concentration were positively correlated in on a maintenance diet (r=0.920, P<0.05) than on a below maintenance diet and an above maintenance diet (r=0.6881, P>0.05 and r=0.50, P>0.05). Response-relationship between faecal and plasma progesterone concentration profiles was non-linear (R-square=0.25, P>0.05) for ewes on an above maintenance diet and linear for a below maintenance diet and a maintenance diet (R-square=0.46, P<0.05 and R-square=0.84, P<0.05). Faecal progesterone can be used as an alternative method of monitoring the ovarian activity in ruminant animals on a maintenance level of feeding.